PENGARUH BIMBINGAN, KEDISIPLINAN, BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR DEPARTEMEN AGAMA - Sutarno, Tri Waspodo & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT The organization goal reach and organization management more effective and efficient while job performance officer’s support. In fact, job performance every office influence by guidance, work discipline, organization culture and leadership. Goal of the research is knowing influence guidance, work discipline, organization culture and leadership to officer’s job performance on Departemen Agama of Karanganyar Regency by partially and together, and to know among guidance, work discipline, organization culture and leadership that dominant influence to officer’s job performance on Departemen Agama of Karanganyar Regency. The research take location on Departemen Agama officers of Karanganyar Regency with the reason problem at the officer’s job performance. Population and samples of the research is all officer on Departemen Agama of Karanganyar Regency counted 51. Collecting data doing with anquete, observation, bibliografi and documentation. Analyze data technique is multiple regression, t test, F test dan determination test Result of t test is guidance, work discipline, organization culture and leadership to officer’s job performance on Departemen Agama of Karanganyar Regency influence partially. Result of F test that guidance, work discipline, organization culture and leadership to officer’s job performance on Departemen Agama of Karanganyar Regency influence together. That is variation of officer’s job performance influence by guidance, work discipline, organization culture and leadership. Keywords : work discipline, organization culture, leadership, job performance